PERSEPSI PEMUSTAKA TERHADAP PUSTAKAWAN DALAM PELAYANAN REFERENSI DI PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA YOGYAKARTA - Choiriyah Choiriyah (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2017)
This study aims to determine the level of user perceptual categories of the librarian in reference service. By knowing user perception, it can be used as a donation of thought and consideration for the performance of the librarian in the library in order to make the services in the reference at the Library of the State Islamic University Sunan Kalidjaga is as maximal as user expectation. The type of this research is quantitative research. The sample number of this research is 100 users which take from the user that uses the service of reference or population. The sample was taken by accidental sampling method. The researcher collected the data by using questionnaire, observation, interviews, and documentation. While the analysis of the data used descriptive quantitative data analysis. Based on the description of the results of research on the user perception in the librarian reference service at the Library of the State Islamic University Sunan Kalidjaga, it can be concluded that the general perception of user to the librarian in the reference service can be categorized into good category with the score of grand mean; 2.64. While the indicator score for the librarians who find information to answer a specific question, can be good category with a grand mean score; 2.70. For the second indicator, librarians help users find the information was categorized into good category with a grand mean score; 2.70. The third indicator, librarians guide users in using library resources and how to conduct research were categorized into good category with a grand mean score; 2.53. This results indicate that there are no indicators that the score of the grand mean is 3:26 to 4:00 or excellent category, it means that the management of library and librarians in the Library of the State Islamic University of Yogyakarta Sunan Kalidjaga should maintain and improve its performance in serving the users at State Islamic University of Yogyakarta Sunan Kalijaga